2005
DOI: 10.1016/j.ydbio.2004.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of the central nervous system in embryonic Drosophila is inhibited by blocking hemocyte migration or neural activity

Abstract: Condensation is a process whereby a tissue undergoes a coordinated decrease in size and increase in cellular density during development. Although it occurs in many developmental contexts, the mechanisms underlying this process are largely unknown. Here, we investigate condensation in the embryonic Drosophila ventral nerve cord (VNC). Two major events coincide with condensation during embryogenesis: the deposition of extracellular matrix by hemocytes, and the onset of central nervous system activity. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(154 citation statements)
references
References 66 publications
10
144
0
Order By: Relevance
“…The secretion of extracellular matrix by hemocytes appears to be particularly important for VNC condensation, as disrupting hemocyte migration impairs both the deposition of extracellular matrix around the VNC and VNC condensation (Olofsson and Page, 2005). Intriguingly, in addition to the PNA reactivity associated with the amnioserosa and VNC, we noticed PNA staining on scattered cells whose number and distribution suggested that they correspond to hemocytes.…”
Section: C1galta and Processes Implicated In Vnc Condensationmentioning
confidence: 71%
See 1 more Smart Citation
“…The secretion of extracellular matrix by hemocytes appears to be particularly important for VNC condensation, as disrupting hemocyte migration impairs both the deposition of extracellular matrix around the VNC and VNC condensation (Olofsson and Page, 2005). Intriguingly, in addition to the PNA reactivity associated with the amnioserosa and VNC, we noticed PNA staining on scattered cells whose number and distribution suggested that they correspond to hemocytes.…”
Section: C1galta and Processes Implicated In Vnc Condensationmentioning
confidence: 71%
“…To facilitate characterization of VNC condensation, we examined animals in which GFP was expressed in the VNC under nrv2-Gal4 or elavGal4 control. In wild-type, condensation begins during stage 15, and continues through hatching (Olofsson and Page, 2005). In C1GalTA mutants, VNC condensation occurs, but fails to reach the same extent of condensation as in wild-type, as the VNC is obviously elongated in first instar larvae ( Fig.…”
Section: C1galta Is Required For Nervous System Morphogenesismentioning
confidence: 88%
“…The following fly strains were used in this study: gcm N7-4 (Vincent et al, 1996); moody ⌬17 ; nrxIV 4304 (Baumgartner et al, 1996); nrxIV EP604 ; nrg 14 (Bloomington Stock Center, Bloomington, IN); nrv2 k13315 (Genova and Fehon, 2003); coracle 5 (Lamb et al, 1998); Df(3R)ED5020 to remove contactin (Faivre-Sarrailh et al, 2004); sinu NWU7 (Wu et al, 2004); Df(1)RR79 to remove the Claudin CG6398; Df(2R)M60E to remove the Claudin CG3770; Df(2R)nap2 to remove the Claudin CG1298; Df(3R)Excel6192 to remove the Claudin CG6982; pck EA97 (megatrachea) (Behr et al, 2003); 454 NeurexinIV:GFP, 125 Lachesin:GFP (Edenfeld et al, 2006); 173 nervana2:GFP (U. Lammel, unpublished observations); UAS:GFP; UAS:laminGFP; UAS:flp, nervana2Gal4 (Bloomington stock center); pvr 7.1 Viking:GFP (Olofsson and Page, 2005); 43Gal4 (Bloomington stock center); c527Gal4 (Hummel et al, 2002); FasIIGal4 (Mz507 ) (B. Altenhein, personal communication); chaGal4 (Salvaterra and Kitamoto, 2001);and SPG:Gal4 (Bainton et al, 2005). All deficiencies were obtained from the Bloomington stock collection.…”
Section: Methodsmentioning
confidence: 99%
“…In mutants with reduced hemocyte motility no lamella is formed (supplemental Fig. 1C, available at www.jneurosci.org as supplemental material) (Olofsson and Page, 2005).…”
Section: The Neural Lamellamentioning
confidence: 99%
“…To study the Drosophila hemocyte lineages, we first used time-lapse confocal microscopy to investigate the expression pattern of the embryonic hemocyte compartment specific croquemort-GAL4 (crq-GAL4) driver [active in embryonic macrophages (Olofsson et al, 2005 and Fig. 1A)] and the Dorothy-GAL4 (Dot-GAL4) driver [expressed in the embryonic lymph gland (Kimbrell et al, 2002 and Fig.…”
Section: Definition Of Embryonic Hemocyte Drivers For Lineage Tracingmentioning
confidence: 99%